Если желания не сбудутся: [роман] / Алла Полянская - Полянская Алла (От ненависти до любви, 2017)
Экземпляры: аб. (2023) / Инвентарный номер: 59101 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 54 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44